A starting point of the assessment of accident tolerant fuels - Marino, Armando Carlos; Furlano, Lucas; Demarco, Gustavo; Baruj, Alberto Leonardo; Mosca, Hugo Osvaldo; Jaroszewicz, Sebastian; Losada, Edith Lorena; Bozzolo, G.; Yawny, Alejandro Andres; Dari, Enzo Alberto (International Atomic Energy Agency, 2020)
Fil: Marino, Armando Carlos. Comisión Nacional de Energía Atómica. Centro Atómico Bariloche; Argentina. Comisión Nacional de Energía Atómica. Gerencia del Área de Energía Nuclear. Instituto Balseiro; Argentina